2008
DOI: 10.5551/jat.e542
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association between Aldehyde Dehydrogenase 2 (ALDH2) Variation and High-Density Lipoprotein Cholesterol (HDL-C) Among Non-Drinkers in Two Large Population Samples in Japan

Abstract: Aim:Moderate alcohol consumption appears to confer some protection against coronary heart disease, which is related to an increase in high-density lipoprotein cholesterol (HDL-C). The genotype of aldehyde dehydrogenase 2 (ALDH2) is closely related to alcohol metabolism but a relationship between ALDH2 genotypes and HDL-C levels has not been proven. We undertook a large-scale correlation study between HDL-C levels and ALDH2 genotype among Japanese non-drinkers to investigate the possibility that HDL-C levels co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
0
21
1
Order By: Relevance
“…Since female drinkers tend to have a moderate amount of alcohol consumption (Figure S1), the observed sexual dimorphism could be explained by a dosedependent interaction between ALDH2 rs671 and HDL-C concentrations. Another Japanese study 33 reported the association between ALDH2 504Lys and low HDL-C concentrations among non-drinkers; while there was the same direction of association (β=-1.36 mg/dl, AG vs. GG), the estimated effects of ALDH2 rs671 genotype for HDL-C concentrations did not reach a nominal significance level in the present study ( Table 2 and Table S6). In contrast to HDL-C levels, LDL-C levels were significantly decreased among drinkers as compared to non-drinkers in the general population panel, in accordance with the previous report in the Japanese.…”
Section: Discussioncontrasting
confidence: 62%
“…Since female drinkers tend to have a moderate amount of alcohol consumption (Figure S1), the observed sexual dimorphism could be explained by a dosedependent interaction between ALDH2 rs671 and HDL-C concentrations. Another Japanese study 33 reported the association between ALDH2 504Lys and low HDL-C concentrations among non-drinkers; while there was the same direction of association (β=-1.36 mg/dl, AG vs. GG), the estimated effects of ALDH2 rs671 genotype for HDL-C concentrations did not reach a nominal significance level in the present study ( Table 2 and Table S6). In contrast to HDL-C levels, LDL-C levels were significantly decreased among drinkers as compared to non-drinkers in the general population panel, in accordance with the previous report in the Japanese.…”
Section: Discussioncontrasting
confidence: 62%
“…A genetic variant that decreases ALDH2 activity, the ALDH2 polymorphism, is transmitted in an autosomal additive manner and is common in the Asian population. Wada et al (2008) found no variants of rs671 in a Caucasian population.…”
Section: Introductionmentioning
confidence: 83%
“…The mechanisms underlying this association have not been fully clarified, but may be explained based on the following reasons. First, the A allele was previously reported to be associated with lower serum high-density lipoprotein-C levels independently of alcohol consumption in Japanese subjects (Wada et al, 2008), so the ALDH2 rs671 polymorphism may influence the risk of CAD at least in part through its effects on serum high-density lipoprotein-C levels. Moreover, the ALDH2 rs671 polymorphism may increase the risk of CAD by increasing intracellular asymmetric dimethylarginine levels (Guo et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Japanese women carrying the ALDH2 G/G homozygous genotype displayed reduced serum levels of lipid peroxides even after adjustment for alcohol intake. 25 Guo et al 26 evaluated HDL-C levels in nondrinking subjects of Chinese Han origin, and found that the homozygous rs671 A/A genotype was associated with significantly lower HDL-C concentrations compared with G/G homozygotes.…”
Section: Discussionmentioning
confidence: 99%